2014
DOI: 10.3390/ijms151018892
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiles Reveal Diverse Responsive Signaling Pathways in Kernels of Two Maize Inbred Lines with Contrasting Drought Sensitivity

Abstract: Drought stress is a major factor that contributes to disease susceptibility and yield loss in agricultural crops. To identify drought responsive proteins and explore metabolic pathways involved in maize tolerance to drought stress, two maize lines (B73 and Lo964) with contrasting drought sensitivity were examined. The treatments of drought and well water were applied at 14 days after pollination (DAP), and protein profiles were investigated in developing kernels (35 DAP) using iTRAQ (isobaric tags for relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 73 publications
2
42
0
Order By: Relevance
“…The protein-protein interaction network analysis indicated that glutathione S-transferase had interactions with six proteins, suggesting its important role in antioxidative defense. Other studies indicated that the expression levels of glutathione S-transferase and glutathione peroxidase were scarcely affected in drought-tolerant maize genotypes but were significantly increased in drought-sensitive maize genotypes under drought conditions (Benešová et al, 2012; Yang et al, 2014). Taken together, these results show that the cooperative relations among the antioxidative proteins play an important role in redox homeostasis under drought conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The protein-protein interaction network analysis indicated that glutathione S-transferase had interactions with six proteins, suggesting its important role in antioxidative defense. Other studies indicated that the expression levels of glutathione S-transferase and glutathione peroxidase were scarcely affected in drought-tolerant maize genotypes but were significantly increased in drought-sensitive maize genotypes under drought conditions (Benešová et al, 2012; Yang et al, 2014). Taken together, these results show that the cooperative relations among the antioxidative proteins play an important role in redox homeostasis under drought conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Xylanase inhibitor proteins are believed to play a role in plant defensive reactions (Dornez et al, 2010; Vasconcelos et al, 2011). A previous study indicated that the expression levels of dehydrin and xylanase inhibitor protein 1 were barely affected in the drought-tolerant maize line Lo964 but were significantly increased in the drought-sensitive line B73 under drought conditions (Yang et al, 2014). In the maize drought-tolerant CE704 and drought-sensitive 2023 genotypes, the expression of dehydrin RAB-17 was increased under drought stress, but the increase was greater in CE704 than in the 2023 genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isobaric tags for relative and absolute quantification (iTRAQ) is a robust mass spectrometry of protein quantitative technology, which can perform relative and absolute quantification in up to eight samples in parallel (Bindschedler and Cramer, 2011; Glibert et al, 2014). Recently, iTRAQ has been widely used for large-scale quantitative plant proteomic studies in exploration of various metabolic processes at the post-transcriptional level (Kambiranda et al, 2013; Martínez-Esteso et al, 2013) in response to various stresses (Yang et al, 2014; Li et al, 2015; Fu et al, 2016). Additionally, iTRAQ-based proteomics has been proven as a powerful method for unraveling the molecular regulatory networks involved in interactions between heavy metals and plant species, and a set of HM-responsive candidate proteins have been successfully identified.…”
Section: Introductionmentioning
confidence: 99%